Overlapping activators and repressors delimit transcriptional response to receptor tyrosine kinase signals in the Drosophila eye. - Xu, C.; Kauffmann, R.C.; Zhang, J.; Kladny, S.; Carthew, R.W. (Cell, 2000)
Regulated transcription of the prospero gene in the Drosophila eye provides a model for how gene expression is specifically controlled by signals from receptor tyrosine kinases. We show that prospero is controlled by signals from the EGF receptor DER and the Sevenless receptor. A direct link is established between DER activation of a transcription enhancer in prospero and binding of two transcription factors that are targets of DER signaling. Binding of the cell-specific Lozenge protein is also required for activation, and overlapping Lozenge protein distribution and DER signaling establishes expression in a subset of equivalent cells competent to respond to Sevenless. We show that Sevenless activates prospero independent of the enhancer and involves targeted degradation of Tramtrack, a transcription repressor.